2017
DOI: 10.1103/physreva.96.063622
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature behavior of the Bose polaron

Abstract: We consider a mobile impurity immersed in a Bose gas at finite temperature. Using perturbation theory valid for weak coupling between the impurity and the bosons, we derive analytical results for the energy and damping of the impurity for low and high temperatures, as well as for temperatures close to the critical temperature $T_c$ for Bose-Einstein condensation. These results show that the properties of the impurity vary strongly with temperature. In particular, the energy exhibits a non-monotonic behavior cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…We also find that the splitting at negative energies disappears at weak boson-impurity interactions for sufficiently large n 1/3 a B . Such behavior is consistent with weak-coupling perturbation theory in the regime a B a, where no splitting is observed [23]. Finally, we see that the spectral weight around zero energy becomes suppressed with increasing n 1/3 a B .…”
Section: Effect Of Boson Interactionssupporting
confidence: 88%
See 1 more Smart Citation
“…We also find that the splitting at negative energies disappears at weak boson-impurity interactions for sufficiently large n 1/3 a B . Such behavior is consistent with weak-coupling perturbation theory in the regime a B a, where no splitting is observed [23]. Finally, we see that the spectral weight around zero energy becomes suppressed with increasing n 1/3 a B .…”
Section: Effect Of Boson Interactionssupporting
confidence: 88%
“…For the finite-temperature Bose polaron, most of the theoretical investigations have been perturbative in nature, being only valid in the limit of weak boson-impurity interactions [23,24,36,37] or at high temperatures well above the BEC critical temperature [38]. While a nonperturbative functional determinant approach has been used for Rydberg atoms in a Bose gas [39,40], the Rydberg polaron differs significantly from the canonical Bose polaron where the impurity is point-like.…”
Section: Introductionmentioning
confidence: 99%
“…Here, λ B/rel are the thermal de Broglie wavelengths at the boson and the reduced mass, respectively. At weaker interaction strengths where σ ∼ a 2 , the above relation for Γ yields a non-universal rate Γ ∝ a 2 T 2 [16,41]. Experimentally, the spectral width drops rapidly for the weaker interaction strengths probed here, down to our resolution limit, prohibiting us from discerning the scaling with temperature (see Fig.…”
mentioning
confidence: 89%
“…For a direct estimate of the quasiparticle decay rate, we can look towards precise results obtained for Bose polarons in the weakly interacting regime where 1/k n |a| 1 [41]. There, it was found that in the presence of a BEC, at T < T C , the polaron decay is driven by thermally excited bosonic quasiparticles.…”
Section: Estimate Of the Impurity Decay Ratementioning
confidence: 99%
See 1 more Smart Citation